2019
DOI: 10.1039/c9na00638a
|View full text |Cite
|
Sign up to set email alerts
|

Accurate electromechanical characterization of soft molecular monolayers using piezo force microscopy

Abstract: We report a new methodology for the electromechanical characterization of organic monolayers based on the implementation of dual AC resonance tracking piezo force microscopy (DART-PFM) combined with a sweep of an applied DC field under a fixed AC field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…The molecular spring constants can, in principle, be obtained experimentally and there have been several studies on their direct measurement [30][31][32][33][34] . For example, in the work of Xu et al 33 , the spring constants of two small molecules, 1,8-octanedithiol and 4,4'-bipyridine, were measured in a setup consisting of two gold electrodes and a molecular junction.…”
Section: J O U R N a L Na Mementioning
confidence: 99%
See 1 more Smart Citation
“…The molecular spring constants can, in principle, be obtained experimentally and there have been several studies on their direct measurement [30][31][32][33][34] . For example, in the work of Xu et al 33 , the spring constants of two small molecules, 1,8-octanedithiol and 4,4'-bipyridine, were measured in a setup consisting of two gold electrodes and a molecular junction.…”
Section: J O U R N a L Na Mementioning
confidence: 99%
“…For example, in the work of Xu et al 33 , the spring constants of two small molecules, 1,8-octanedithiol and 4,4'-bipyridine, were measured in a setup consisting of two gold electrodes and a molecular junction. Similarly, the contact stiffness of small molecule ligands, bio-inspired peptide and peptoid oligomers was estimated by using atomic force microscopy 34 . different linker molecules.…”
Section: J O U R N a L Na Mementioning
confidence: 99%
“…The phase curve resembles a rectangle and displays a nearly 180° phase hysteresis, which can rule out the influence of electrostatic forces on the signal. 46 The monolayer VP nano-sheet has inherent dipoles since there is no space charge there. 47 Therefore, by providing a voltage of roughly 18 V in SS-PFM mode, the polarity of the monolayer VP nano-sheet can be changed.…”
Section: Resultsmentioning
confidence: 99%
“…[23,24] While it has been demonstrated that amino acids and peptides are piezo-active, [5] significant challenges exist in applying them to usable devices, including aligning the materials or crystals to produce a bulk piezoelectric response by means of an external high-voltage electric field. [5] We find self-assembled monolayers (SAMs) to be a promising approach to bulk alignment of piezoelectric molecules [25,26] and thus present piezoelectric SAM (PSAM) devices based on selfassembled oligopeptide monolayers. SAMs have been widely studied, and thiol-containing molecules are known to form uniform, stable monolayers on gold substrates.…”
mentioning
confidence: 99%
“…[23,24] While it has been demonstrated that amino acids and peptides are piezo-active, [5] significant challenges exist in applying them to usable devices, including aligning the materials or crystals to produce a bulk piezoelectric response by means of an external high-voltage electric field. [5] We find self-assembled monolayers (SAMs) to be a promising approach to bulk alignment of piezoelectric molecules [25,26] and thus present piezoelectric SAM (PSAM) devices Flexible, biocompatible piezoelectric materials are of considerable research interest for a variety of applications, but many suffer from low response or high cost to manufacture. Herein, novel piezoelectric force and touch sensors based on self-assembled monolayers of oligopeptides are presented, which produce large piezoelectric voltage response and are easily manufactured without the need for electrical poling.…”
mentioning
confidence: 99%